Film forming polymeric ionic liquids (PILs) based on polybenzimidazoles for CO2 separation - Kumbharkar, Santosh C.; Bhavsar, Rupesh S.; Kharul, Ulhas K. (RSC Advances, 2014)
PILs are emerging as promising materials for CO2 capture. Film formation, which is a requisite for membrane formation, is induced in a family of PILs by N-substituting a rigid thermo-mechanically stable polybenzimidazole, followed by metathesis. This provided two IL groups per repeat unit of the PIL and enhanced the CO2 separation characteristics.